Analisis Korespondensi Data Kriminologi Polresta Makassar Barat - Suhena Suhena (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2017)
This research aims to apply analysis correspondences in interpreting crimes that occurred in the Polresta Makassar Barat based on data obtained from local police agencies from July 2013 to July 2014. Correspondence analysis is a data analysis technique that is demonstrated through the rows and columns simultaneously from a contingency table bi-direction in low dimension vector. The variables involved in the analysis is a crime scene, time and age category. In Chi-Square analysis process obtained the result that there is no relation between crimes and age category. From the value the correspondence analysis between the crimes and a time of occurrence, obtained a value of inertia to the dimension of the first and second row are 74.10% and 24.30%. This means data obtained were able to explain the variability of the data amounted to 57% of total inertia. Based on the results of the output data plot between the crimes and times of occurrence can be explained that theft with violence and drugs tend to happen at 12:00-17:00 as for the theft of motor vehicles and heavy persecution tends to occur at 18:00-06:15.